Dynamics among Nations: The Evolution of Legitimacy and Development in Modern States - Hilton L. Root (The MIT Press, 2013)
Nature’s evolutionary processes have generated a burgeoning area of inquiry, the study of complexity, which examines how environments and their constituent parts continuously adapt to and transform one another. Complex systems, found everywhere from rain forests to ant colonies to birds in flight, can help us understand how complexity also arises in socioeconomic systems, which is the subject of this book. Descriptions of international relations routinely concede complexity, but not in the scientific sense. Employed here, complexity is a property of systems comprising many interdependent parts, arising when the behavior of the whole emerges from the interactions of its components. A change in one part of the system affects other parts until the system acquires new properties that its individual components did not possess. Thus, to understand the collective behavior of a social system, and how it arises from the relationships of its constituent parts, one must think about systems in ways that differ significantly from conventional approaches to solving large-scale social problems. Shifts in trade and in geopolitical influence have created new networks and brought about an interconnectedness of the world’s many social and economic systems that exist at different stages of development. These networks are not only interconnected, they are constantly reacting to the behaviors, or anticipated behaviors, of other networks that are also repositioning themselves as the landscape they share is altered. Together they shape the larger system, creating rules and identities at the macro level that differ from those at the micro levels.Interdependence among connected but diverse parts is a characteristic that distinguishes complex from merely complicated systems. In a complex system, the removal of a single part will change the behaviors of the remaining components; in a merely complicated system, such as a clock or a nuclear reactor, the removal of one part will not cause a change in the remaining parts, although the system itself may cease to function. Complex systems may be organized hierarchically, but they can also selforganize without design, making it impossible to predict the behaviors of numerous components in constantly shifting environments and organization formations. What happens in one component may affect seemingly unrelated components, so distinguishing cause and effect is not easy